Categories of supply chain performance indicators: an overview of approaches - Leończuk, Dorota (Business, Management and Economics Engineering, 2016)
The increasing complexity of supply chains, whose structure is changing from a linear to network form creates the need to track a growing amount of information allowing the evaluation of the functioning of the entire supply chain. Developing a system for measuring the performance of the supply chain requires the proper selection of indicators. Performance measurement should be done in a particular context, the analysed dimensions of indicators resulting from the purpose and focus of the survey should be determined. The article reviews Polish and foreign literature in terms of the proposed framework and methods for measuring the performance of the supply chain and the indicated categories (dimensions) of indicators. The authors approach the subject of evaluation of the performance of the supply chain in very different ways. Indicators are divided according to the level of the decision-making process: strategic, tactical, and operational. They are also divided into cost and non-cost or financial and non-financial ones. There are also approaches using the already well established methods and models. An example of this is the selection of perspectives according to the Balanced Scorecard (BSC) and the SCOR model.